Innovative Learning Arts and Culture during the Pandemic in Junior High School - Ari Irfan Fahruddin; Agus Cahyono (Institut Seni Indonesia Surakarta, 2022)
The online learning is a new thing in learning cultural arts at Islamic Junior High School Al-Azhar BSB City Semarang, it is an interesting and challenging things because of the presence of students who come from several different places. During the COVID-19 pandemic, the teacher applied several different methods to make students more pro-active and think critically. Innovation begins with changing learning strategies, learning patterns and assessments in the learning process. This study aims to determine learning innovations in cultural arts subjects during the COVID-19 pandemic by using a qualitative descriptive approach method which interviews directly with teacher at Al-Azhar 29 Islamic Junior High School, BSB City Semarang. Data analysis using data triangulation with data processing techniques using data reduction, display data and conclusions. The results of this study indicate the existence of innovations in learning cultural arts at Al-Azhar 29 Islamic Junior High School, BSB City Semarang, including; improving learning strategies, learning media, learning management, and critical assessment systems for students.